Planting Southern Pines in Florida - Elysia Lewis; Michael Andreu; Chris Demers (EDIS)
Florida landowners have contributed vastly to the Southeast’s planting of pines over many decades; recent incentive programs across the state have encouraged further interest. Understanding the factors that affect seedling quality and survival of native pine species will assure a more successful and productive forest plantation. This publication reviews each southern pine's important silviculture characteristics, soil-site conditions, and potential markets and products. It outlines planting standards and techniques as they relate to landowners’ objectives and their target markets. It is to be used as a guide to facilitate selection of appropriate pine species and offers guidance on best practices for handling seedlings throughout all stages of tree planting.